EXTH-50. IDENTIFYING TRIM11 AS A POTENTIAL THERAPEUTIC TARGET FOR MALIGNANT GLIOMAS. (14th November 2022) - Di, Kaijun; Abrams, Daniela; Yadav, Pratik; Das, Bhaskar; Bota, Daniela
Abstract: TRIM11 (tripartite motif-containing protein 11) belongs to the TRIM/RBCC (the RING B-box coiled-coil) family of E3 ubiquitin ligases. Members of this family have been implicated in development, neurodegenerative diseases, cellular response to viral infection and cancer. Glioblastoma (GBM) is an aggressive infiltrative brain tumor with poor prognosis. Our previous work demonstrated that TRIM11 is over-expressed in high-grade gliomas and promotes proliferation, invasion, migration and tumor growth, suggesting TRIM11 is a target for malignant glioma treatment. Here we reported the effect of TRIM11 on GBM progression in vivo using immunocompromised mice intracranially implanted with GBM xenografts over-expressing TRIM11. The control group mice survived longer than the mice bearing TRIM11 over-expressing xenografts (P< 0.5), suggesting TRIM11 enhances tumor progression in vivo . The oncogenic effect of TRIM11 may be related to its influence on apoptosis pathway as a robust induction of poly (ADP-ribose) polymerase (PARP) was observed in TRIM11 over-expressing GBM cells. PARP could repair DNA damage caused by UV light, radiation, and certain anticancer drugs, etc. Blocking PARP may prevent cancer cells from repairing their damaged DNA, causing them to die. Temozolomide (TMZ) is a standard-of-care chemotherapeutic agent for GBM through alkylating/methylating DNA, leading to DNA damage and death of tumor cells. TRIM11 over-expressing GBM cells were found more resistant to TMZ and showed a higher survival rate compared to parental cells, indicating that TRIM11 might be a therapeutic target for GBM. Based on homology modeling we designed and synthesized small library of TRIM11 inhibitors, and identified one compound (BT# 592) significantly inhibited the growth of GBM cells in a dose-dependent manner, implicating that TRIM11 inhibitors may serve as novel agents for malignant glioma treatment. We are in the process to develop more active compounds using SAR studies to identify hit-to-lead compounds as potential therapeutics for GBM.